Upaya Keberatan Atas Putusan Arbitrase Bpsk Jakarta Berdasarkan Undang-Undang Nomor 8 Tahun 1999 (Studi Kasus Putusan Bpsk No. 099/Pts.A/Bpsk-Dki/Ii/2012) - Riski Ananda; Mustolih Siradj (Faculty of Sharia and Law State Islamic University Syarif Hidayatullah Jakarta, 2022)
The purpose of this study is to ascertain consumer protection under the Jakarta BPSK Arbitration judgment through an examination of a car purchasing and selling case involving business actors PT. Nissan Motor Indonesia and their customer Ludmilla Arief. The purpose of this study is to examine the regulations governing advertising used by business actors to deceive customers. Additionally, it attempts to examine and compare the BPSK Arbitration ruling about consumer protection in the context of deceptive advertising. Through a law and case perspective, this study employs empirical legal research methods and literature. The findings indicated that the Arbitration Award's (BPSK) legal basis, namely Article 9 Paragraph (1) letter k and Article 10 of Law No. 8 of 1999, was consistent with the Consumer Protection Law's requirements. As a result, PT. Nissan Motor Indonesia is liable for consumer losses under Article 19 of the Consumer Protection Act.